ONLINE DISPUTE RESOLUTION (ODR) SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA BISNIS DI INDONESIA - Yonata, Yohan (Universitas Sains dan Teknologi Komputer, 2025)
This research analyzes The increase in business transactions in the digital era has led to the birth of complex business disputes that require quick and efficient resolution. This study aims to analyze the urgency of regulating Online Dispute Resolution (ODR) in Indonesia, its potential benefits, and implementation challenges. Using a normative juridical approach and descriptive-qualitative analysis, this study focuses on national regulations, such as Law No. 30/1999 on Arbitration and Alternative Dispute Resolution and ITE Law, which although relevant, have not regulated the technical implementation of ODR in detail. The results show that ODR offers cost and time efficiency, accessibility without location restrictions, and flexibility in choosing a dispute resolution forum. However, challenges such as legal disparities between countries, limited technological infrastructure, and personal data protection are significant obstacles. This research confirms that specific ODR regulations are needed to provide legal certainty and support effective online dispute resolution, especially in the context of cross-border e-commerce. With proper regulation, ODR can become an innovative and competitive alternative to dispute resolution in Indonesia.